2007
DOI: 10.1002/fld.1626
|View full text |Cite
|
Sign up to set email alerts
|

Steady and unsteady laminar flows of Newtonian and generalized Newtonian fluids in a planar T‐junction

Abstract: SUMMARYAn investigation of laminar steady and unsteady flows in a two-dimensional T-junction was carried out for Newtonian and a non-Newtonian fluid analogue to blood. The flow conditions considered are of relevance to hemodynamical applications and the localization of coronary diseases, and the main objective was to quantify the accuracy of the predictions and to provide benchmark data that are missing for this prototypical geometry. Under steady flow, calculations were performed for a wide range of Reynolds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…(26) to Eq. (29) originally proposed by Rhie and Chow [4], which can efficiently eliminate the spurious pressure wiggles on collocated grids.…”
Section: Discretization Of the Convection Termmentioning
confidence: 98%
See 1 more Smart Citation
“…(26) to Eq. (29) originally proposed by Rhie and Chow [4], which can efficiently eliminate the spurious pressure wiggles on collocated grids.…”
Section: Discretization Of the Convection Termmentioning
confidence: 98%
“…In the past years, Neofytou [24,25] used the SIMPLE method coupled with the QUICK scheme on collocated structured grids for generalized Newtonian fluid flows of Power-Law, Bingham, Quemada and Casson models. Miranda et al [26] employed the FVM in conjunction with SIMPLE on non-uniform structured grids for Newtonian and generalized Newtonian fluid flows in a planar T-junction. Tomé et al [27] developed an FVM method coupled with the SMAC method on staggerd structured grids to simulate the 2D generalized Newtonian free surfaces flow.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure to extract pressure drop data from CFD results closely follows the work by El-Shaboury et al [22], who focused on the heat transfer in 2D dividing T-junctions. The work of Miranda et al [23] also deals with 2D dividing T-junctions and details the process followed for the simulation.…”
Section: Set-up Of Pressure Drop Correlationsmentioning
confidence: 99%
“…Some modern studies [8][9][10][11] showed precise structure of pressure change in branch pipe or T-joint. Many of these studies, however, considered flow of liquid.…”
Section: Introductionmentioning
confidence: 99%